Studies towards the stereoselective synthesis of alkenes - Arif, T (2011)
The work presented in this thesis mainly describes the development of new reactions of β-lithiooxyphosphonium ylides to access stereodefined substituted alkenes in a highly convergent fashion. Firstly, β-lithiooxy ylides prepared from aldehydes and phosphonium ylides were shown to react with halogen electrophiles to provide a highly stereoselective route to E-alkenyl bromides and iodides. This methodology was successfully applied to the first total synthesis of naturally occurring (5E,9Z)-6-bromohexadeca-5,9-dienoic acid. Secondly, an experimentally straightforward method was developed for the stereocontrolled formation of trisubstituted Z-allylic esters by in situ trapping of β-lithiooxyphosphonium ylides with readily available halomethyl esters. The synthetic utility of this methodology was demonstrated with the synthesis of plaunotol [(2Z,6E)-2-((E)-4,8-dimethylnona-3,7-dien-1-yl)-6-methylocta-2,6-diene-1,8-diol] and the first asymmetric synthesis of the naturally occurring geranylgeraniol-derived diterpene (6S,7R,Z)-7-hydroxy-2-((E)-6-hydroxy-4-methylhex-4-enylidene)-6,10-dimethylundec-9-enyl acetate. Furthermore, the chemistry of β-lithiooxyphosphonium ylides was expanded to access synthetically useful disubstituted Z-allylic esters. The synthetic utility of Z-allylic esters was also demonstrated in a versatile and diastereoselective Ireland-Claisen rearrangement to access γ,δ-unsaturated acids. Finally, the synthesis of the side-chain of the 6,7-dideoxysqualestatin H5 was also investigated. It was demonstrated that the side-chain of 6,7-dideoxysqualestatin H5 could be accessed by a convergent and stereoselective organozinc-based strategy